The Voyage of discovery : a historical introduction to philosophy - Lawhead, William F. (United States of America : Cengage Learning Asia Pte Ltd, 2015)
Using metaphors, analogies, images, and common experiences, this title presents an introduction to the history of Western philosophy that illustrates philosophy as an intellectual process and not simply a collection of opinions or conclusions.
Part I. the ancient period -- Part II. the middle ages -- Part III. the modern period -- Part IV. the contemporary period.
Includes index.
Keywords: PHILOSOPY